APPLICATION OF STROBOSCOPIC POINCARE MAP FOR ROTOR SYSTEM INTERFACE NODE DEFECTS DIAGNOSIS - Mikhail V. Chuveyko (Advanced Engineering Research, 2011)
The application of stroboscopic Poincare map for the recovery of normal path of dynamic system motion in case of peak additive disturbance and in absence of a priori data on frequency of restorable signal is considered.